Integrated readings for the urban green roof. Expressive codes and forms of nature - Alberto Bologna; Adriana Ghersi; Stefano Melli (Agathón)
The quality of public space requires new study paradigms: interconnected pieces of a broader urban green system can guarantee ecosystem services and liveability to spaces full of cultural meaning and social attraction. In particular, green roof gardens, by guaranteeing new connections with the context, prove to be a new strategic possibility to give value and space to nature, looking at the built city as a living system. An increasingly frequent, sometimes generative element of the language of the ‘third digital green industrial revolution’, green roof gardens have provided a compositional, formal and ornamental response to the need to save energy and reduce the consumption of materials and natural resources on a city-wide scale, as well as that of architecture, in different climatic and socio-technical contexts. This contribution intends to analyse green roof gardens as a strategic element for the overall regeneration of the urban system and as an architectural element identifying the design culture of our time.